“PENGARUH INDEPENDENSI AUDITOR, EMOTIONAL QUOTIENT DAN PROFESIONALISME AUDITOR TERHADAP KUALITAS AUDIT PADA BPKP PROVINSI BENGKULU” - Adinda Luthfia Thomas Hoswandi; Irwansyah Irwansyah (ITB AAS Indonesia Surakarta, 2024)
The aim of this research is to determine the influence of auditor independence, emotional quotient and auditor professionalism on audit quality at the Bengkulu Province BPKP with a total of 60 people and a sample of 53 respondents. In this research, quantitative methods were used to test hypotheses and the data was processed by Smart PLS 3.00. The results of this research show that auditor independence shows that it has no effect on audit quality, while emotional satisfaction and auditor professionalism show that it has an effect on audit quality.